Assessment of total phenolic content, antioxidative property and hepatoprotective potential of aqueous extract of Momordica charantia L - Mohammad Amil Zulhilmi Benjamin; Ayesha Ahmed; Mohammad Iqbal (Malaysian Society for Biochemistry & Molecular Biology (MSBMB), 2025)
Momordica charantia L. (Cucurbitaceae) has a longstanding history in traditional medicine for its potential protective effects against various ailments including oxidative stress. This study explores the hepatoprotective activity of the aqueous extract of M. charantia (AEMC) against carbon tetrachloride (CCl4)-induced liver injury in rats. Total phenolic content (TPC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity were measured as part of the evaluation. The four groups of male Sprague-Dawley rats were randomly assigned as follows: normal group, control or CCl4-treated group (1.0 mg/kg b.wt.), and AEMC-pretreated groups (doses of 125 and 250 mg/kg b.wt.). After a 14-day duration, all rats were humanely euthanized, and the hepatoprotective potential of AEMC was assessed through biochemical analyses and histopathological examinations of liver tissue. The results revealed that the low TPC (46.64 ± 1.59 mg GAE/g db) and the weak DPPH activity (IC50 = 975.00 µg/mL) of AEMC played a significant role in its robust antioxidant activities. Moreover, AEMC demonstrated significant reductions in alanine aminotransferase and aspartate aminotransferase, leading to changes in enzyme levels (3–15% recovery), indicating an increase in reduced glutathione levels (17–36% recovery), a decrease in malondialdehyde levels (30–49% recovery), and an enhancement in the levels of catalase (19–31% recovery), glutathione peroxidase (15–26% recovery), glutathione reductase (11–18% recovery), glutathione S-transferase (24–34% recovery), and quinone reductase (3–16% recovery). Histopathological examinations of liver tissue also revealed that AEMC led to reduced lipid alterations, hepatocyte derangement, and inflammatory cell infiltration in rats treated with CCl4. AEMC demonstrates potent antioxidant properties and provides substantial protection against the hepatic damage caused by CCl4 in rats.